2021
DOI: 10.3390/math9192389
|View full text |Cite
|
Sign up to set email alerts
|

Contracting and Involutive Negations of Probability Distributions

Abstract: A dozen papers have considered the concept of negation of probability distributions (pd) introduced by Yager. Usually, such negations are generated point-by-point by functions defined on a set of probability values and called here negators. Recently the class of pd-independent linear negators has been introduced and characterized using Yager’s negator. The open problem was how to introduce involutive negators generating involutive negations of pd. To solve this problem, we extend the concepts of contracting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Batyrshin et al [2] and Batyrshin [3] showed many properties of independent negators and of affine-linear negators with generating function f (p) = a + bp with a = f (0) and b = f (1) − f (0). It is easy to verify that affine-linear negators are independent.…”
Section: Independence and Linearitymentioning
confidence: 99%
See 4 more Smart Citations
“…Batyrshin et al [2] and Batyrshin [3] showed many properties of independent negators and of affine-linear negators with generating function f (p) = a + bp with a = f (0) and b = f (1) − f (0). It is easy to verify that affine-linear negators are independent.…”
Section: Independence and Linearitymentioning
confidence: 99%
“…Furthermore, we speak of an independent negator if the corresponding negation is independent. This formulation also follows Batyrshin [3].…”
mentioning
confidence: 93%
See 3 more Smart Citations